2008
DOI: 10.1177/1744987107086099
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the attributes of threshold and higher level nursing practice for children's cancer and palliative care nurses: the views of children, their parents and other stakeholders

Abstract: Bradford Scholars -how to deposit your paper Overview Copyright check• Check if your publisher allows submission to a repository.• Use the Sherpa RoMEO database if you are not sure about your publisher's position or email openaccess@bradford.ac.uk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 9 publications
2
2
0
Order By: Relevance
“…While nurses traditionally consider technical tasks and procedures as their primary professional obligation ( Milton, 2002 ), the adolescents indicated a need for stronger individual focus. This is in keeping with the conclusion of Hale et al that both children and parents found that the “strongest and most effective nursing” was exercised by nurses who “introduced themselves not only as professionals, but also as real people” ( Hale, Long, Sanderson, & Carr, 2008 ). Their study indicates that the adolescents' foremost expectation of the nurse concerns their personal or attitudinal characteristics, such as honesty, empathy, patience, friendliness, and humor, combined with supporting, attentive, and communicating behavior.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…While nurses traditionally consider technical tasks and procedures as their primary professional obligation ( Milton, 2002 ), the adolescents indicated a need for stronger individual focus. This is in keeping with the conclusion of Hale et al that both children and parents found that the “strongest and most effective nursing” was exercised by nurses who “introduced themselves not only as professionals, but also as real people” ( Hale, Long, Sanderson, & Carr, 2008 ). Their study indicates that the adolescents' foremost expectation of the nurse concerns their personal or attitudinal characteristics, such as honesty, empathy, patience, friendliness, and humor, combined with supporting, attentive, and communicating behavior.…”
Section: Discussionsupporting
confidence: 86%
“…Their study indicates that the adolescents' foremost expectation of the nurse concerns their personal or attitudinal characteristics, such as honesty, empathy, patience, friendliness, and humor, combined with supporting, attentive, and communicating behavior. The findings of Hale et al (2008) are thus corroborated by our informants' remarks about the “nice” or “fantastic” nurses who exhibited understanding, empathy, and presence without apparently being restricted by time.…”
Section: Discussionsupporting
confidence: 71%
“…The presence of any given structure or type of follow-up care did not result in a greater likelihood of any other structure or follow-up being present. However, findings from the initial study phases, as well as recent findings [ 29 , 33 – 38 ] from others, indicated a need for greater attention to these structures of care and to bereavement follow-up when assessing quality of end-of-life care for children. Items comprising the Structures of Care and Provide Bereavement Follow-up domains were retained as stand-alone items with good content and face validity.…”
Section: Resultsmentioning
confidence: 99%
“…29,30 Parents preferred to interact with health professionals who had good communication and interpersonal skills, 27,29,31-36 including compassion, 23,24,36,37 gentle concern, 4,38 care and sensitivity particularly when breaking bad news, 24,29,35,36,[38][39][40][41] and a sense of humor. 30,38,42 Simple acts of smiling, making eye contact, showing emotion, and initiating physical contact were appreciated by parents and fostered connections with the health professional. 27,40,43,44 Parents appreciated when health professionals took the time to get to know all family members, including siblings, and their situation apart from that related to the ill child.…”
Section: Connectingmentioning
confidence: 99%